Returns to Teaching Repetition - The Effect of Short-Term Teaching Experience on Student Outcomes - Harold E. Cuffe; Jan Feld; Trevor O'Grady (Institute of Labor Economics (IZA), 2019)
Teachers often deliver the same lesson multiple times in one day. In contrast to year-to-year teaching experience, it is unclear how this teaching repetition affects student outcomes. We examine the effects of teaching repetition in a setting where students are randomly assigned to a university instructor's first, second, third or fourth lesson on the same day. We find no meaningful effects of repetition on grades, course dropout, or study effort and only suggestive evidence of positive effects on teaching evaluations. These results suggest that teaching repetition is a powerful tool to reduce teachers' preparation time without negative effects on students.
Keywords: I21; I23; 330; higher education; teaching repetition; teacher experience